A Comparison of Permanent Anchors Versus Biodegradable Anchors and Tacks for Arthroscopic Shoulder Stabilization. Issue 1 (March 2018) - Peters, Karin S.; Pirapakaran, Kajan H.; Pearce, Adrian; Murrell, George A.C.
Abstract : To determine the clinical outcomes of arthroscopic stabilization of patients with anterior glenohumeral instability using knotless devices made from 4 different materials. A prospective cohort study was performed on patients who had an arthroscopic anterior shoulder stabilization for unidirectional anterior instability by a single surgeon using one of 4 devices: Suretac resorbable tac made of PGA (n=41), BioKnotless resorbable suture anchor made of PLLA (n=52), the OPUS Labrafix knotless anchor made from stainless steel (n=18), and the Pushloc knotless anchor made from PEEK (n=44). Standardized patient-determined and examiner-determined outcomes were obtained before operation and 6, 12, 24 weeks, and up to 10-year follow-up. Kaplan-Meier analysis for redislocation showed a fall in survival curves from 1 year (90% stable) to 3 years (40% stable) in the Suretac group then a plateau to 10 years; and a fall in stability survivorship for the Bioknotless group from 1 year (90% stable) to 5 years (60% stable). Survivorship curves for the 2 nonresorbable anchors were more encouraging with over 90% stable out to 3 years (Pushloc) and 4 years (Labrafix) ( P <0.001). Arthroscopic stabilization for traumatic anterior instability leads to excellent outcomes when using nonresorbable knotless devices (6% and 5% recurrence at 3 to 5 y). The resorbable suture anchors and tacs in this study showed a higher recurrence rate (40% and 60%, respectively) at 5 years.